THE REACTION OF THE INDONESIAN CAPITAL MARKET TO THE INCREASING FUEL PRICES (BBM) IN INDONESIAN COMPOSITE INDEX (IHSG) - Fitriaty Fitriaty; Muhammad Haris Saputra (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
The purpose of this study was to test the capital market's reaction to the announcement of an increase in fuel prices on the composite stock price index through testing differences in returns and trading volume before and after the fuel price increase on September 3, 2022. This research uses an event study approach, the sample in this study is the stock price index. combination during the event period. The results of this study show that the capital market reacted to the fuel price hike event on September 3, 2022. There are differences in market returns and trading volume on the composite stock price index before and after the fuel price increase, which indicates that the fuel price increase has an influence on market movements capital in Indonesia, this is due to the significant increase in fuel prices at the time of the observation event